THE IMPACT OF DIGITAL FINACIAL INCLUTION ON THE SUSTAINABLE FINANCE OF THE MSME SECTOR IN THE LHOKSEUMAWE CITY REGION WITH MODERATION OF THE BANKING SERVICE MODEL - Muhammad Multazam; Rico Nur Ilham; Muttaqien; Ayu Anora; Teuku Muhammad Iqbal (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This research determines how the Banking Model strengthens/weakens the impact of Perceived Usefulness, Perceived Financial Cost and Perceived Ease of Use on Sustainable Finance SMEs. This type of research is quantitative descriptive. The population is all MSMEs in Lhokseumawe City, totaling 2,354 MSMEs. This study uses the Taro Yamane formula with a precision level set at 10% with a total sample size of 96. The results reveal that Perceived Usefulness positively and insignificantly affects Sustainable Finance SMEs, Perceived Financial Cost positively and significantly affects Sustainable Finance SMEs, Perceived Ease of Use positively and significantly affects Sustainable Finance SMEs, Banking Model positively and insignificantly affects Sustainable Finance SMEs, Banking model can strengthen the influence of Perceived Usefulness on Sustainable Finance SMEs, Banking model can strengthen the effect of Perceived Financial Cost to Sustainable Finance SMEs, and Banking models can weaken the influence of Perceived Ease of Use on Sustainable Finance SMEs.